Cloning, expressing, and purification of riboflavin synthase from photobacterium sp. j15 - Dorrazehi, Gol Mohammad (2014)
Riboflavin synthase (RiS) is a homotrimeric enzyme that catalyzes the final reaction of riboflavin (vitamin B2) biosynthesis from two molecules of 6,7-dimethyl-8- ribityllumazine. Gram-negative bacteria and certain yeasts are unable to absorb riboflavin or riboflavin derivatives from the environment. The RiS is nonexistent in humans while it only presents in bacteria and yeasts, which are dependent on their own production of riboflavin and will not survive in lack of the RiS function; hence the RiS is a potential target for the development of antimicrobial agents to target Gram-negative pathogens. The aim of this research was to clone and express the RiS in heterologous system and investigate the oligomerization of the RiS monomers. The RiS in current study is from a Malaysian isolated strain, Photobacterium sp. strain J15. Protein sequence alignment of this RiS shows high similarity to the RiS of E. coli. Analysis of the DNA sequence of this riboflavin synthase shows 6 rare codons, in which common E. coli strains are not able to supply the corresponding tRNAs, thus the E. coli strain Rosetta-gami B (DE3) pLysS was selected as the expression host. The gene encoding RiS was cloned into pET-32b(+) vector, which carried ampicillin resistance gene and utilized T7 promoter for high-level expression of a Trx-His tagged protein. The heterologous expression of RiS was performed by transformation of recombinant pET-32b(+) vector into E. coli Rosetta-gami B(DE3)pLysS. High-level expression of soluble RiS was optimized for expression temperature at 20 °C, inducer (IPTG) concentration at 1 mM, and time of induction for 20 h. The purification of the His-tagged enzyme was performed by affinity chromatography and was subjected to western-blot for verification. The purified fusion enzyme was cleaved by thrombin to remove Trx-His tag and purified by anion exchange chromatography to get the mature enzyme. Specific activity of mature RiS was significantly higher than fusion RiS. The size of mature RiS was estimated as 26.5 kDa by gel filtration chromatography. Site directed mutagenesis of I190V and chimerization of RiS was experimented to improve the trimer formation of quaternary structure of RiS but it didn not affect the trimerization of monomers, therefore, formation of trimer of RiS monomers was confirmed by cross-linking experiments. A melting point of 42.3 °C and a secondary structure composition of 13.6 % helix, 25.1 % beta, 12.5 % turn and 38.5 % random was measured by Circular-dichroism (CD) analysis. Through this work the RiS of Photobacterium sp. J15 was successfully cloned and expressed into heterologous system. The RiS is found to function only in dimeric or trimeric form. The availability of functional enzyme by heterologous expression enables further characterization and structural studies towards drug development at pharmaceutical level.